Nonlinear Oscillations of an Articulated Pipe System Subjected to Oil Flow and External Excitations - Dai, L.; Wang, Y. Zhang, X.; Huang, T. (Journal of Applied Nonlinear Dynamics, 2026)
Articulated pipes conveying fluids are widely used in industries especially petroleum industries. The nonlinear oscillations of an articulated pipe jointed with an oil conveying system is studies and characterized in this research. The responses of the articulated pipe without external excitation are analyzed. The oscillations of the pipe corresponding to the fluid flow and joint stiffness are investigated in detail. The nonlinear oscillations of the pipe subjected to external excitation are also studied in this research. The periodic, quasi-periodic and chaotic oscillations of the pipe are found in the study. The nonlinear behaviors of the pipe’s responses are diagnosed and characterized with employment of the Periodicity Ratio (P-R) method. A regularirregular region diagram is developed corresponding to wide ranges of system parametric values, reflecting those used in engineering practices. The results of the research provide practically sound guidance for industrial application and research in this field.